Documentation (International review of mission, 1978)
A Pastoral Letter from Colin Winter, Bishop of the Diocese in exile, Robert Mize, 6th Bishop of Damaraland, Richard Wood, assistant bishop in exile, Edward Morrow, Vicar General and James Kauluma, suffragan bishop of Damaraland.